THE STRUCTURE AND POSITION OF THE ORTHODONTIC MINI-IMPLANT AND THEIR INFLUENCING FACTORS ON THE TRAUMA TO THE CORTICAL BONE PLATE DURING ORTHODONTIC LOADING - Shaienko, D.P.; Stetsuk, Ye.V.; Smahliuk, L.V.; Shepitko, V.I.; Smahliuk, V.I. (World of Medicine and Biology, 2025)
Orthodontic implants, as the skeletal anchorage systems, are widely used by orthodontists due to their property to minimize the impact on the patient’s teeth. To identify the factors influencing the contact area between the orthodontic implant and bone, as well as bone resorption around the orthodontic implant. The experimental study compared two methods of orthodontic implant placement: leaving the implant’s threaded part in the cortical bone plate and inserting the implant’s neck into the bone. Using the same pressure on adjacent implants, the condition of the bone surrounding them was assessed. Leaving the implant’s threaded portion within the cortical bone plate increases its damage and the implant’s mobility under applied load. A smooth surface with an expanded neck of orthodontic implants provides a larger and denser contact with the cortical bone plate, which distributes the orthodontic load more effectively, thereby reducing the traumatic impact on bone tissue under force application.